Antibiofilm Potential of Alpha-Amylase from a Marine Bacterium, Pantoea agglomerans. (15th April 2022) - Goel, Charu; Shakir, Chippu; Tesfaye, Azene; Raghavanpillai Sabu, Kuzhunellil; Idhayadhulla, Akbar; Manilal, Aseer; Woldemariam, Melat; Vijayan, Nayana; Shah, Shabna
Abstract : Bacterial biofilms are a big menace to industries and the environment and also in the health sector, accumulation of which is a major challenge. Despite intensive efforts to curb this issue, a definitive solution is yet to be achieved. Enzyme-templated disruption of the extracellular matrix of biofilm and its control and elimination are emerging as an efficient and greener strategy. The study describes the antibiofilm potential of alpha-amylase from the marine microorganism Pantoea agglomerans PCI05, against food-borne pathogens. Amylase exhibited stability in a wide pH range and retained 50% of its activity at temperatures as high as 100°C. Thermal analysis of the enzyme produced showed thermal stability, up to 130°C. From these findings, it can be envisaged that the alpha-amylase produced from P. agglomerans can be used for starch liquefaction; it was also evaluated for antibiofilm activity. Amylase from this marine bacterium was found to efficiently disrupt the preformed biofilms of food-borne pathogens such as Bacillus cereus, Serratia marcescens, Vibrio parahaemolyticus, Listeria monocytogenes, and Salmonella enterica enterica serotype Typhi based on the value of biofilm inhibitory concentrations.